Controllable drug uptake and nongenomic response through estrogen-anchored cyclodextrin drug complex - Yin JJ (Dove Medical Press, 2015)
Juan-Juan Yin,1,2 Stepan P Shumyak,2 Christopher Burgess,2 Zhi-Wei Zhou,2 Zhi-Xu He,3 Xue-Ji Zhang,4 Shu-Ting Pan,2,5 Tian-Xin Yang,6 Wei Duan,7 Jia-Xuan Qiu,5 Shu-Feng Zhou21Xiaolan People’s Hospital, Southern Medical University, Zhongshan, Guangdong, People’s Republic of China; 2Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA; 3Guizhou Provincial Key Laboratory for Regenerative Medicine, Stem Cell and Tissue Engineering Research Center and Sino-US Joint Laboratory for Medical Sciences, Guizhou Medical University, Guiyang, Guizhou, 4Research Center for Bioengineering and Sensing Technology, University of Science and Technology Beijing, Beijing, 5Department of Oral and Maxillofacial Surgery, the First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 6Department of Internal Medicine, University of Utah and Salt Lake Veterans Affairs Medical Center, Salt Lake City, UT, USA; 7School of Medicine, Deakin University, Waurn Ponds, VIC, AustraliaAbstract: Breast cancer is a leading killer of women worldwide. Cyclodextrin-based estrogen receptor-targeting drug-delivery systems represent a promising direction in cancer therapy but have rarely been investigated. To seek new targeting therapies for membrane estrogen receptor-positive breast cancer, an estrogen-anchored cyclodextrin encapsulating a doxorubicin derivative Ada-DOX (CDE1-Ada-DOX) has been synthesized and evaluated in human breast cancer MCF-7 cells. First, we synthesized estrone-conjugated cyclodextrin (CDE1), which formed the complex CDE1-Ada-DOX via molecular recognition with the derivative adamantane-doxorubicin (Ada-DOX) (Kd=1,617 M-1). The structure of the targeting vector CDE1 was fully characterized using 1H- and 13C-nuclear magnetic resonance, mass spectrometry, and electron microscopy. CDE1-Ada-DOX showed two-phase drug-release kinetics with much slower release than Ada-DOX. The fluorescence polarization analysis reveals that CDE1-Ada-DOX binds to recombinant human estrogen receptor α fragments with a Kd of 0.027 µM. Competition assay of the drug complex with estrogen ligands demonstrated that estrone and tamoxifen competed with CDE1-Ada-DOX for membrane estrogen receptor binding in MCF-7 cells. Intermolecular self-assembly of CDE1 molecules were observed, showing tail-in-bucket and wire-like structures confirmed by transmission electronic microscopy. CDE1-Ada-DOX had an unexpected lower drug uptake (when the host–guest ratio was >1) than non-targeting drugs in MCF-7 cells due to ensconced ligands in cyclodextrins cavities resulting from the intermolecular self-assembly. The uptake of CDE1-Ada-DOX was significantly increased when the host–guest ratio was adjusted to be less than half at the concentration of CDE1 over 5 µM due to the release of the estrone residues. CDE1 elicited rapid activation of mitogen-activated protein kinases (p44/42 MAPK, Erk1/2) in minutes through phosphorylation of Thr202/Tyr204 in MCF-7 cells. These results demonstrate a targeted therapeutics delivery of CDE1-Ada-DOX to breast cancer cells in a controlled manner and that the drug vector CDE1 can potentially be employed as a molecular tool to differentiate nongenomic from genomic mechanism.Keywords: breast cancer, drug vector, functionalized, membrane estrogen receptor, polysaccharide, targeted drug delivery